Sample maze tests for assessing the reading performance of grade three pupils - Marbella, Azulina Detera 1942- (1976)
To answer the need for a reliable testing instrument for assesing and monitoring the reading performance of Grade Three pupils in the Division of Sorsogon, a set of tests using the Maze Technique was constructed.The readability of the selections was determined through the Spache Readability Formula for selections from Kindergarten to Grade Three, and the Dale and Chall Readability Formula for Grade Four and Grade Five. To find out the reliability and validity of the maze tests, they were administered to 50 pupils from Magsaysay South Central School. A manual was included in the paper to help the reading teacher in administering the tests.
"December, 1976."
Vita.
Thesis (M.A.T. Reading)--University of the Philippines, Diliman.
Keywords: Maze tests -- Philippines -- Sorsogon; Reading comprehension -- Philippines -- Sorsogon -- Ability testing